The Relationship Between The Level Of Knowledge Of Posyandu Cadres And Early Detection Skill Growth In Toddlers In Mojosari Village And Bleber Village - Titik Juwariyah; Jajuk Winarni; Lailaturohmah Lailaturohmah; Ratna Mildawati (Universitas Pahlawan Tuanku Tambusai, 2020)
The growth of toddlers is something that needs attention because stunted growth can interfere with physical growth, intelligence, and brain development. Therefore, the knowledge and skills of posyandu cadres in the early detection of toddler growth are very much needed. The aim of this research was to determine the relationship between the level of knowledge of posyandu cadres and early detection skills of toddler growth in Mojosari Village and Bleber Village. The research design used Correlational Analytics with a Cross-Sectional approach. The population of this study was 30 posyandu cadres, the sample was 30 posyandu cadres using a total sampling technique. The research instrument uses an observation sheet. Data were analyzed using the Spearman Rho Test. The research results showed that the level of knowledge of Posyandu cadres was mostly good knowledge, with as many as 19 respondents (63.3%). Meanwhile, the majority of early growth detection skills in toddlers were good, with as many as 21 respondents (70.0%). The results of the analysis show that there is a relationship between the level of knowledge of posyandu cadres and early growth detection skills in toddlers in Mojosari Village and Bleber Village (p-value = 0.00; ? <0.05). Early detection in children is very necessary to find that the child's growth is disturbed or experiencing illness. Increasing the knowledge of posyandu cadres can help health workers detect early the growth process of children during posyandu activities.